1992
DOI: 10.1111/j.1751-1097.1992.tb04252.x
|View full text |Cite
|
Sign up to set email alerts
|

A Biofilm Used as Ultraviolet‐dosimeter

Abstract: Abstract— A UV‐dosimeter has been developed for routine measurements which mainly weights the various components of the spectrum in relation to their damaging effects on a microorganism. For this purpose a biofilm was constructed, comprising dried spores of Bacillus subtilis (wild‐type or DNA repair defective strain), immobilized on transparent polyester plastic sheets. After irradiation, the biofilm was incubated in a growth medium. The proteins, synthesized by the immobilized microorganisms after spore germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 15 publications
1
52
0
1
Order By: Relevance
“…Additionally, mats were exposed to unfiltered solar radiation and also placed under UG-5 filters (Schott, Mainz, Germany), which almost completely absorb PAR but exhibit a high transmission below 400 nm, allowing both UV-A and UV-B to pass. Canopies exposed to unfiltered solar radiation were equipped with biological UVdosimeters (Viospor, Biosense, Germany; see Quintern et al (1992) and Furusawa et al (1998) for reference) under Ulva layer one, two and three (see Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, mats were exposed to unfiltered solar radiation and also placed under UG-5 filters (Schott, Mainz, Germany), which almost completely absorb PAR but exhibit a high transmission below 400 nm, allowing both UV-A and UV-B to pass. Canopies exposed to unfiltered solar radiation were equipped with biological UVdosimeters (Viospor, Biosense, Germany; see Quintern et al (1992) and Furusawa et al (1998) for reference) under Ulva layer one, two and three (see Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Further attempts to extend this spore dosimetry include the comparisons of dose-rate profiles at several sites in the northern hemisphere (120) and continuous monthly biomonitoring at several sites, including the tropics (121). More recently, a dosimetric system based on measuring protein synthesis during germination of UV-irradiated B. subtilis spores immobilized in a biofilm and subsequent growth has been developed (158) and was used to measure the biologically harmful effects of the increase in UV flux accompanying the seasonal appearance of the "ozone hole" over Antarctica. This study demonstrated that spore dosimetry can indeed detect changes in the depth of the ozone layer, but again a simple response of the dosimeter to changes in ozone column thickness was insufficient to explain all of the phenomena observed (159).…”
Section: Monitoring the Ozone Layer With Spore Dosimetersmentioning
confidence: 99%
“…Biologically effective irradiances as a function of the simulated ozone column thickness were measured with B. subtilis spores immobilized in a biofilm (158) and compared to expected irradiances, using radiative transfer calculations and the biofilm action spectrum. After the mission, the biofilms were incubated and stained, and optical densities indicative of the biological activity were determined for each exposure condition by image analysis.…”
Section: Monitoring the Ozone Layer With Spore Dosimetersmentioning
confidence: 99%
“…To gain a quantitative assessment of the implications of progressive ozone depletion for life on Earth, extraterrestrial solar radiation was used in a space experiment as a natural on May 9, 2018 by guest http://mmbr.asm.org/ UV source to irradiate spores of Bacillus subtilis 168 in a biological dosimeter "biofilm" (109). This biofilm technique directly weights the incident spectral components of the environmental UV radiation according to their biological effectiveness (179,210,211). During the German Spacelab mission D2 (Tables 1 and 3), precalibrated "biofilms" consisting of dry monolayers of immobilized spores of B. subtilis 168 were exposed for defined intervals to extraterrestrial solar radiation that was filtered through an optical filtering system to simulate different ozone column thicknesses down to very low values.…”
Section: Role Of the Stratospheric Ozone Layer In Protecting Earth'smentioning
confidence: 99%